The optimization of personalized ventilation based on a jogger's unsteady breathing cycle. (February 2019) - Xu, Xinyue; Li, Zhengrong; Zhao, Jinpeng
Abstract: Jogging is increasingly popular as a robust activity. However, the concentration of the exhaled carbon dioxide exposes to human during the outdoor exercise. Thus, the healthy air supply is in growing demand. By changing vertical and horizontal locations and air supply rate, an additional airflow field can alter the performance of local ventilation. This work assumes the addition of an auxiliary personalized ventilation device (PV), under various specific air supply rates, distances and angles to investigate the optimization of concentration dissipation and microclimate promotion. The results show the flow field characteristics and concentration distribution in respiration area under an unsteady breathing process. Based on the orthogonal test, the condition with those determined parameters (the supply velocity: 3m/s, distance from the nostrils: 2cm and the angle: + 20 °) has the optimal performance. Moreover, the velocity of air supply is the primary factor among other factors that influence the performance of pollutant removal, through the sensitive test.